2017
DOI: 10.1002/anie.201706647
|View full text |Cite
|
Sign up to set email alerts
|

Observation and Identification of an Atomic Oxygen Structure on Catalytic Gold Nanoparticles

Abstract: Interactions between oxygen and gold surfaces are fundamentally important in diverse areas of science and technology. In this work, an oxygen dimer structure was observed and identified on gold nanoparticles in catalytic decomposition of hydrogen peroxide to oxygen and water. This structure, which is different from isolated atomic or molecular oxygen surface structures, was observed with in situ surface-enhanced Raman spectroscopic measurements and identified with density functional theory calculations. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 30 publications
4
37
0
Order By: Relevance
“…Similarly constructed periodic surfaces with similar computational settings were previously used successfully for studying adsorption and reactions on Ni [13] and other metal surfaces. [14][15][16][17][18][19][20][21][22][23] Adsorption energies were calculated at 0 K without zero-point energy corrections using as a reference the sum of energies for the corresponding clean surface and an isolated propylene molecule calculated separately. Adsorption energies are reported as positive numbers, À ΔE ads .…”
Section: Methodsmentioning
confidence: 99%
“…Similarly constructed periodic surfaces with similar computational settings were previously used successfully for studying adsorption and reactions on Ni [13] and other metal surfaces. [14][15][16][17][18][19][20][21][22][23] Adsorption energies were calculated at 0 K without zero-point energy corrections using as a reference the sum of energies for the corresponding clean surface and an isolated propylene molecule calculated separately. Adsorption energies are reported as positive numbers, À ΔE ads .…”
Section: Methodsmentioning
confidence: 99%
“…The density of states was calculated with 1 empty band and a k-point grid of 2 Â 2 Â 1.The computational settings were similar to those that were previously used successfully to describe molecular properties of surface functional groups, including hydroxyls. [54][55][56][57][58] The rGO structure was modeled as an infinite slab constructed using a periodic unit cell. Edge sites were not considered in the model because they represented less than 0.2% of all carbon atoms due to the large size of our rGO sheets (300-800 nm).…”
Section: H Dispersion-corrected Density Functional Theory (Dft-d) Calculationsmentioning
confidence: 99%
“…As an example, our study with monodisperse 5, 50 and 400 nm Au particles showed that the rate of catalytic H 2 O 2 decomposition increased dramatically with decreasing Au particle size when the total number of surface Au atoms was kept constant. 7,8 For adsorbates, experimental and computational studies demonstrate that adsorption energies and, consequently, geometries and vibrational frequencies of atomic and molecular oxygen on Au surfaces are highly dependent on the size of Au particles. [7][8][9] As an example, while molecular oxygen on Au(111) is unstable, its adsorption becomes progressively more energetically favorable with decreasing Au particle size.…”
mentioning
confidence: 99%